Tracking Public Interest Through Google Trends: Comparative Analysis of Global Movements - Nanayakkara, Amila; B.T.G.S.Kumara; R.M.K.T.Rathnayaka (Journal of Computers and Digital Business, 2024)
This paper examined the digital dynamics of three significant social justice movements: Black Lives Matter (2020), South African unrest (2021), and Mahsa Amini protests (2022) through the lens of Google Trends analysis. By tracking search interest patterns during key events, the study explored how each movement gained momentum and sustained visibility online. The analysis revealed distinct public engagement patterns for each movement: The Black Lives Matter movement experienced global peaks in search interest, with sustained attention driven by discussions on police reform and racial justice. The South African unrest saw sharp, localized spikes in search activity, particularly during moments of heightened tension such as the looting incidents and the government’s deployment of the military. The Mahsa Amini protests demonstrated sustained, high-level interest globally, with search trends reflecting the growing international focus on human rights and state repression in Iran. The findings highlighted how search engines like Google played a pivotal role in amplifying these movements, documenting societal reactions, and shaping the global public discourse. This study underscored the power of digital platforms to reflect and influence the trajectory of social movements across different political and cultural contexts.